Menumbuhkan Sikap Disiplin Siswa (Analisis terhadap Praktik Kerjasama Antara Guru di SMA Negeri 5 Pamekasan) - Agustina, Nur Yulia (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determine the form of cooperation between counseling teachers and Islamic religious education teachers in fostering student discipline at SMA Negeri 5 Pamekasan. The approach used is a qualitative approach to the type of case study research. The data collection techniques used included three techniques, namely interview techniques, observation techniques and documentation techniques for two data sources, namely primary data (BK teachers and PAI) and secondary data (students and supporting documents at SMA Negeri 5 Pamekasan). After that, the data was analyzed using the stages of data reduction, data analysis and drawing conclusions. The findings in this study indicate that the form of cooperation between Counseling Teachers and Islamic Religious Education Teachers in Growing Student Discipline Attitudes at SMA Negeri 5 Pamekasan is already good by practicing coordinated performance and evaluative